2013
DOI: 10.1002/ange.201208593
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxorhodium/Chiral Diene Complexes as Effective Catalysts for the Asymmetric Arylation of 3‐Aryl‐3‐hydroxyisoindolin‐1‐ones

Abstract: The transition-metal-catalyzed enantioselective alkylation and arylation of imines is a versatile means of accessing a-chiral amines, which are important structural components of a number of biologically active compounds, and there have been many reports of the successful catalytic enantioselective addition of organometallic reagents to imines derived from aldehydes. [1] In contrast, the asymmetric addition of organometallic reagents to ketimines, which provides chiral a-tertiary amines, remains less developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…As to the enantioselective construction of chiral 3,3disubstituted isoindolin-1-ones,m any elegant methods have been developed based on either organocatalysis [4] or transition-metal catalysis. [5] However,t he substrates were mainly limited to 3-hydroxyisoindolinones,a lkenyl benzamides,a nd N-halobenzoyl indoles.W hereas transition-metal-catalyzed CÀHa ctivation has shown great potential [6] in terms of expanding the structural diversity of available isoindolinone motifs,asymmetric variants remain extremely rare and highly challenging. [7] In 2013, Nishimura and co-workers developed an iridium/diene-catalyzed [3+ +2] annulation by C À Ha ctivation that afforded spiroisoindolinones from 3-aryl-3-hydroxyisoindolinones and 1,3-dienes.…”
mentioning
confidence: 99%
“…As to the enantioselective construction of chiral 3,3disubstituted isoindolin-1-ones,m any elegant methods have been developed based on either organocatalysis [4] or transition-metal catalysis. [5] However,t he substrates were mainly limited to 3-hydroxyisoindolinones,a lkenyl benzamides,a nd N-halobenzoyl indoles.W hereas transition-metal-catalyzed CÀHa ctivation has shown great potential [6] in terms of expanding the structural diversity of available isoindolinone motifs,asymmetric variants remain extremely rare and highly challenging. [7] In 2013, Nishimura and co-workers developed an iridium/diene-catalyzed [3+ +2] annulation by C À Ha ctivation that afforded spiroisoindolinones from 3-aryl-3-hydroxyisoindolinones and 1,3-dienes.…”
mentioning
confidence: 99%
“…The cyclic N-sulfonyl imines used as the arylation substrates are classified into aldimines and ketimines, of which the former are in general more reactive than the latter and some of the ketimines substituted with electron-withdrawing groups such as ester and CF 3 are as reactive as aldimines. [3][4][5][6] During our studies on the catalytic asymmetric addition of organoboron reagents to carbon-carbon and carbon-heteroatom double bonds, [8,9] we found that a cationic palladium complex containing a chiral phosphine-oxazoline ligand showed high catalytic activity and high enantioselectivity in the asymmetric addition of arylboronic acids to cyclic Nsulfonyl ketimines 1 (R = alkyl, aryl), giving high yields of the corresponding chiral cyclic sulfonamides, which bear a tetrasubstituted stereogenic center. Although the five-membered ring imines are highly reactive, giving the corresponding sultams upon arylation even for ketimines, the ring cleavage giving the corresponding chiral methylamines without loss of enantiomeric purity is not trivial.…”
mentioning
confidence: 99%
“…[2] As a result, their asymmetric synthesis has attracted increasing attention in recent years. Among the established methods for the synthesis of chiral 3,3-disubstituted isoindolinones, [3][4][5][6][7][8][9] a particularly straightforward approach is the catalytic enantioselective addition of nucleophilic partners to cyclic Ncarbonyl ketimines, which were generated in situ by dehydration of 3-hydroxyisoindolinones (Scheme 1b). Followed this concept, the research groups of Zhou [4a] and Gredičak [4b] reported the asymmetric addition of indoles to 3-hydroxyisoindolinone-derived cyclic Ncarbonyl ketimines.…”
mentioning
confidence: 99%
“…Followed this concept, the research groups of Zhou [4a] and Gredičak [4b] reported the asymmetric addition of indoles to 3-hydroxyisoindolinone-derived cyclic Ncarbonyl ketimines. Hayashi and co-workers [5] developed a rhodium-catalyzed asymmetric arylation of 3hydroxyisoindolinones by employing arylboroxines as nucleophiles. Both research groups of Hu [6] and Singh [7] described the asymmetric alkylation of 3hydroxyisoindolinones with oxonium ylides or α-diazo esters.…”
mentioning
confidence: 99%